Perlindungan Hukum Pencurian Data Pribadi dan Bahaya Penggunaan Aplikasi Pinjaman Online - Olifiansyah, Muhammad (DE'RECHTSSTAAT, 2021)
Illegal online loans are widely discussed. The pinjol modes that trap the victim are also increasingly diverse. The Indonesian Consumers Foundation noted that complaints about misuse of personal data are among the most widely reported by the public, either directly or indirectly. Illegal online loans, often called illegal loans. The purpose of this paper is to examine the legal protection of borrowers' personal data in online loan application services. The method used in this paper is a normative legal method with an approach to legislation and a fact approach. The results of the study found that borrowing through illegal online lending does not eliminate the user's debt payment obligations, then there are also comparative results in other countries that can be adopted to overcome this problem of illegal borrowing.